The Influence of Customer Satisfaction Towards Purchase Decision at Cafe Istana Kopi King Medan - Lyvia Limlius; Susanto, Susanto; Lidia Berliana Siboro (Lembaga Pengembangan Kinerja Dosen, 2023)
Hospitality is associated with hospitality organizations. These organizations are aware of the importance of welcoming guests to their organizations. The organizations are expected to develop service principles that are based on hospitable behaviours. Customer satisfaction is an emotional assessment of consumers after consumers use products where the expectations and needs of consumers who use them are met. The purpose of this research is to know whether customer satisfaction have an impact toward purchase decision at Café Istana Kopi King Medan. Research methodology used in this research is descriptive research and causal research. Research methods which used are validity and reliability test, descriptive statistic analysis, normality test, coefficient correlation, coefficient of determinant, simple linear regression analysis and Z testing. Therefore the number of samples for this study amounted to 97 respondents The conclusion of this research is that customer satisfaction has influence on purchase decision at Cafe Istana Kopi King Medan. Based on Z test, it can be obtained that Zcount > Ztable (7.93 > 1.96). It means the hypothesis is accepted that customer satisfaction has impact on purchase decision at Cafe Istana Kopi King Medan. From correlation test, it can be seen that customer satisfaction has moderate positive relationship toward purchase decision in 0.693. In Coefficient determination, the percentage influence of customer satisfaction on purchase decision is 65.5%. It means that 65.5% of purchase decision can be explained by customer satisfaction and the remaining 34.5% is impacted by other factors which are not discussed in this skripsi.